2014
DOI: 10.1155/2014/560120
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Lung Disease in Rett Syndrome

Abstract: Rett syndrome (RTT) is a pervasive neurodevelopmental disorder mainly linked to mutations in the gene encoding the methyl-CpG-binding protein 2 (MeCP2). Respiratory dysfunction, historically credited to brainstem immaturity, represents a major challenge in RTT. Our aim was to characterize the relationships between pulmonary gas exchange abnormality (GEA), upper airway obstruction, and redox status in patients with typical RTT (n = 228) and to examine lung histology in a Mecp2-null mouse model of the disease. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 95 publications
4
21
0
Order By: Relevance
“…Evidence is accumulating that systems additional to the central nervous system are affected in Rett syndrome. The respiratory system is no exception, with evidence of lower airway inflammation and a mismatch in ventilation and perfusion in healthy individuals with Rett syndrome . Ventilation and perfusion mismatch is the most common cause of hypoventilation and shunt resulting in hypoxaemia and could in part be caused by lower airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is accumulating that systems additional to the central nervous system are affected in Rett syndrome. The respiratory system is no exception, with evidence of lower airway inflammation and a mismatch in ventilation and perfusion in healthy individuals with Rett syndrome . Ventilation and perfusion mismatch is the most common cause of hypoventilation and shunt resulting in hypoxaemia and could in part be caused by lower airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in an Italian case series ( n =27) each with observed autonomic breathing abnormalities, abnormal findings on high‐resolution computed tomography scans were identified in over half the cases, with bronchiolectasis identified in one‐third despite no clinically recognizable lung disease . Several years later, the same group identified abnormalities in pulmonary gas exchange in approximately three‐quarters of their study population ( n =228) and reported that a chronic mismatch in ventilation and perfusion seemed related to oxidative stress . In the same study, lung histology was investigated in a mouse model, and diffuse inflammatory infiltrate of the terminal bronchioles and alveoli was identified in two of four MECP2 ‐mutant mice .…”
mentioning
confidence: 97%
“…While many neurodevelopmental conditions are associated with increased respiratory infection due to oropharyngeal dysfunction, it was importantly shown that intrinsic immune defects may underlie these infections in the context of MeCP2 duplication syndrome, supporting a direct role for MeCP2 in epigenetic control of immune cells (Yang et al, 2012). Given the involvement of respiratory infection in MeCP2 duplication syndrome it is interesting to note a recent report that the lungs of Mecp2-null mice display an inflammatory infiltrate, which may contribute to the respiratory phenotypes observed in the context of Mecp2-deficiency (De Felice et al, 2014); this may raise the question as to what role MeCP2 may play more globally in the regulation of immune responses in the respiratory tract. Together, these findings suggest that MeCP2 is critical for healthy immune system function, and therefore warrant further investigation into the possible contributions of the immune system in Rett syndrome.…”
Section: The Immune System and Mecp2mentioning
confidence: 99%
“…It might be the case that lack of MeCP2 in the peripheral tissue produced an effect that is masked by the profound CNS-related phenotype. Indeed there is clinical and mouse data pointing to several phenotypes (bone, liver, lung) that may be peripheral in origin [97][98][99][100][101]. However, delivery of exogenous MECP2 directly to the brain using ssAAV9 [11], emphasizes the crucial role of the brain in ameliorating most of the gross aspects of the phenotype.…”
Section: Global or Local Delivery Of Mecp2mentioning
confidence: 99%